Treatment of equine sarcoids using recombinant poxviruses expressing feline interleukin‐2. Issue 3 (16th March 2021) - Loschelder‐Ostrowski, Johanna; Winter, Judith Christine; Merle, Roswitha; Klopfleisch, Robert; Gehlen, Heidrun
Abstract : Background: Interleukin (IL)‐2 stimulates antitumour immunity and is successfully used for the treatment of different neoplasias. Hypothesis/Objectives: Canarypox virus locally expressing feline IL‐2 is safe and can be used to treat equine sarcoids. Animals: Twenty horses of different breeds with a median age of eight years (interquartile range 6.0–13.3 years) and a total number of 59 sarcoids were included in the study. Methods: In this prospective clinical trial, sarcoids were injected twice seven days apart, with a recombinant canarypox virus expressing feline IL‐2. Complete blood counts (CBC) and fibrinogen levels were measured before treatment and on days 1, 2, 7 and 8. Results: Complete regression was achieved in eight horses (40%) and partial regression in two horses (10%). No change in sarcoid size was observed in two horses (10%) and the disease progressed in five horses (25%). Sarcoids of three horses (15%) showed initial response followed by tumour growth. There were no significant changes in CBC and fibrinogen levels after either injection. One horse developed a mild fever the day after each injection, which subsided without treatment the following day. Conclusions: Treatment of equine sarcoids with recombinant canarypox virus expressing feline IL‐2 seems to be a safe therapy option. Although the expression of IL‐2 after vector injection and its biological activity in horses were not proven in this study, the treatment resulted in regression and partial regression in 50% of the cases. Further studies are necessary to verify these findings and to establish a treatment protocol. Abstract : Background – Interleukin (IL)‐2 stimulates antitumour immunity and is successfully used for the treatment of different neoplasias. Hypothesis/Objectives – Canarypox virus locally expressing feline IL‐2 is safe and can be used to treat equine sarcoids. Conclusions – Treatment of equine sarcoids with recombinant canarypox virus expressing feline IL‐2 seems to be a safe therapy option. Although the expression of IL‐2 after vector injection and its biological activity in horses were not proven in this study, the treatment resulted in regression and partial regression in 50% of the cases. Further studies are necessary to verify these findings and to establish a treatment protocol.). Résumé: Contexte: L'interleukine (IL)‐2 stimule l'immunité anti‐tumorale et est efficacement utilisée pour le traitement de différentes néoplasies. Hypothèses/Objectifs: Canarypoxvirus exprimant localement IL‐2 félin est sûr et peut être utilisé pour traiter les sarcoïdes équins. Sujets: Vingt chevaux de différentes races avec un âge médian de huit ans (écart interquartille de 6.0‐13.3 ans) et un nombre total de 59 sarcoïdes ont été inclus dans l'étude. Méthodes: Dans cette étude clinique prospective, les sarcoïdes ont été injectés deux fois à sept jours d'intervalle avec un canarypoxvirus recombinant exprimant IL‐2 félin. Une formule sanguine (CBC) et les taux de fibrinogènes ont été mesurés avant traitement et à jours 1, 3, 7 et 8. Résultats: Une régression complète a été obtenue pour huit chevaux (40%) et une régression partielle pour deux chevaux (10%). Aucun changement de taille des sarcoïdes n'a été observé pour deux chevaux (10%) et la maladie s'est aggravée pour cinq chevaux (25%). Les sarcoïdes de trois chevaux (15%) ont montré une réponse initiale puis une croissance de la tumeur. Il n'y avait pas de changement significatif dans le CBC et les taux de fibrinogènes après chacune des injections. Un cheval a développé une fièvre modérée le jour après chaque injection, qui disparaissait sans traitement le jour suivant. Conclusions: Le traitement des sarcoïdes équins avec canarypoxvirus exprimant IL‐2 félin semble être une option thérapeutique sure. Bien que l'expression d'IL‐2 après injection du vecteur et son activité biologique chez les chevaux n'aient pas été prouvées dans cette étude, le traitement résultaient en une régression et une régression partielle dans 50% des cas. D'autres études sont nécessaires pour vérifier ces données et pour établir un protocole thérapeutique. Resumen: Introducción: la interleuquina 2 (IL‐2) estimula la inmunidad antitumoral y se utiliza con éxito para el tratamiento de diferentes neoplasias. Hipótesis/Objetivos: El poxvirus de canarios que expresa localmente IL‐2 felina es seguro y puede usarse para tratar sarcoides equinos. Animales: se incluyeron en el estudio veinte caballos de diferentes razas con una mediana de edad de ocho años (rango intercuartílico 6, 0‐13, 3 años) y un total de 59 sarcoides. Métodos: en este ensayo clínico prospectivo, se inyectaron sarcoides dos veces con siete días de diferencia, con un poxvirus de canarios recombinante que expresaba IL‐2 felina. Se midieron los recuentos sanguíneos completos (CBC) y los niveles de fibrinógeno antes del tratamiento y en los días 1, 2, 7 y 8. Resultados: se logró una regresión completa en ocho caballos (40%) y una regresión parcial en dos caballos (10%). No se observó ningún cambio en el tamaño del sarcoide en dos caballos (10%) y la enfermedad progresó en cinco caballos (25%). Los sarcoides de tres caballos (15%) mostraron una respuesta inicial seguida de crecimiento tumoral. No hubo cambios significativos en los niveles de CBC y fibrinógeno después de cualquiera de las inyecciones. Un caballo desarrolló una fiebre leve al día siguiente de cada inyección, que remitió sin tratamiento al día siguiente. Conclusiones: El tratamiento de los sarcoides equinos con el poxvirus de canarios recombinante que expresa IL‐2 felina parece ser una opción terapéutica segura. Aunque la expresión de IL‐2 después de la inyección del vector y su actividad biológica en caballos no se probaron en este estudio, el tratamiento resultó en regresión y regresión parcial en el 50% de los casos. Se necesitan más estudios para verificar estos hallazgos y establecer un protocolo de tratamiento. Zusammenfassung: Hintergrund: Interleukin (IL)‐2 stimuliert die Antitumor Immunität und wird erfolgreich zur Behandlung verschiedener Neoplasien eingesetzt. Hypothese/Ziele: Das Kanarienpoxvirus, welches lokal felines IL‐2 exprimiert ist sicher und kann verwendet werden, um equine Sarkoide zu behandeln. Tiere: Es wurden zwanzig Pferde verschiedener Rassen mit einem medianen Alter von acht Jahren (Interquartilsabstand 6, 0‐13, 3 Jahre) und insgesamt 59 Sarkoide in die Studie aufgenommen. Methoden: Eine völlige Remission wurde bei acht Pferden (40%) erzielt und eine partiale Remission bei zwei Pferden (10%). Es konnte bei zwei Pferden keine Veränderung der Sarkoidgröße beobachtet werden (10%) und bei fünf Pferden verlief die Erkrankung progressiv (25%). Die Sarkoide von drei Pferden (15%) zeigten anfangs eine Verbesserung, gefolgt von vermehrtem Tumorwachstum. Es gab nach der jeweiligen Injektion keine signifikanten Veränderungen bei Blutbild und Fibrinogenwerten. Ein Pferd hatte am Tag nach jeder Injektion ein mildes Fieber, welches ohne Behandlung am darauffolgenden Tag wieder verschwand. Schlussfolgerungen: Eine Behandlung equiner Sarkoide mit rekombinantem Poxvirus, welches felines IL‐2 exprimiert, scheint eine sichere Therapieoption darzustellen. Obwohl die Exprimierung von IL‐2 nach einer Vektorinjektion und seine biologische Aktivität bei Pferden in dieser Studie nicht bestätigt werden konnten, resultierte die Behandlung ini 50% der Fälle in einer völligen bzw partialen Regression. Es sind weitere Studien nötig, um diese Befunde zu verifizieren und um ein Behandlungsprotokoll zu erstellen. 要約: 背景: インターロイキン (IL)‐2 は抗腫瘍免疫を刺激し、さまざまな腫瘍の治療に使用されている。 仮説/目的: ネコIL‐2を局所的に発現するカナリアポックスウイルスは安全で、馬のサルコイドの治療に使用することができる。 被験動物: 年齢中央値が8歳 (中間値範囲6.0~13.3歳) の異なる品種の馬20頭、合計59のサルコイドを研究に含めた。 方法: 本前向き臨床試験では、サルコイドにネコIL‐2を発現する組換えカナリアポックスウイルスを7日間隔で2回注射した。全血球計算(CBC)およびフィブリノーゲン値を治療前、治療後1、2、7、8日目に測定した。 結果: 8頭 (40%) の馬で完全退行が、2頭 (10%) で部分退行を達成した。サルコイドのサイズの変化は2頭 (10%) に認められず、5頭 (25%) で病状が進行した。3頭の馬 (15%) のサルコイドは初期反応を示し、その後腫瘍の増殖が認められた。いずれの注射を行ってもCBCおよびフィブリノゲン値に有意な変化はなかった。1頭の馬は各注射の翌日に軽度の発熱を示したが、翌日には治療せずに治まった。 結論: ネコIL‐2を発現する組換えカナリアポックスウイルスを用いた馬のサルコイド治療は、安全な治療オプションの一つであると思われる。本研究では、ベクター注入後のIL‐2の発現および馬における生物学的活性は証明されなかったが、治療により50%の症例で退行および部分的な退行が得られた。これらの知見を検証し、治療プロトコールを確立するためには、さらなる研究が必要である。 摘要: 背景: 白细胞介素(IL)‐2刺激抗肿瘤免疫, 并成功用于治疗不同的肿瘤。 假设/目的: 局部表达猫IL‐2的金丝雀痘病毒是安全的, 可用于治疗马结节病。 动物: 研究纳入了20匹不同品种的马, 中位年龄为8岁 (四分位距6.0‐13.3岁), 共59种结节病。 方法: 在这项前瞻性临床试验中, 结节病每隔七天注射两次, 用表达猫IL‐2的重组金丝雀痘病毒。在治疗前和第1、2、7和8天检测血常规 (CBC)和纤维蛋白原水平。 结果: 8匹马(40%)达到完全缓解, 2匹马(10%)达到部分缓解。2匹马(10%)未观察到结节病大小变化, 5匹马(25%)疾病有所发展。3匹马(15%)的结节病显示初始缓解, 随后肿瘤生长。两次注射后, CBC和纤维蛋白原水平均无显著变化。1匹马在每次注射后第二天出现轻度发热, 第二天未经治疗退烧。 结论: 用表达猫IL‐2的重组金丝雀痘病毒治疗马结节病, 似乎是一种安全的治疗选择。尽管本研究未证实载体注射后IL‐2的表达及其在马体内的生物活性, 但该治疗使得50%的病例缓解和部分缓解。有必要进行进一步研究, 以验证这些结果并确立治疗方案。 Resumo: Contexto: A interleucina (IL)‐2 estimula a imunidade antitumoral e é utilizada com sucesso no tratamento de diferentes neoplasias. Hipótese/Objetivos: O vírus canarypox que expressa IL‐2 felina localmente é seguro e pode ser usado para tratar sarcóides equinos. Animais: Vinte cavalos de raças diferentes com idade mediana de oito anos (intervalo interquartil 6, 0‐13, 3 anos) e um número total de 59 sarcoides foram incluídos no estudo. Métodos: Neste ensaio clínico prospectivo, o vírus canarypox recombinante expressando IL‐2 felina foi injetado nos sarcoides duas vezes em um intervalo de sete dias. Hemogramas completos (HM) e níveis de fibrinogênio foram mensurados antes do tratamento e nos dias 1, 2, 7 e 8. Resultados: Regressão completa foi obtida em oito cavalos (40%) e regressão parcial em dois cavalos (10%). Nenhuma mudança no tamanho do sarcóide foi observada em dois cavalos (10%) e a doença progrediu em cinco cavalos (25%). Os sarcoides de três cavalos (15%) apresentaram boa resposta inicial seguida de crescimento do tumor. Não houve alterações significativas no hemograma e nos níveis de fibrinogênio após qualquer injeção. Um cavalo apresentou febre moderada no dia seguinte de cada injeção, que cedeu sem tratamento em um dia. Conclusões: O tratamento de sarcóides equinos com vírus canarypox recombinante que expressa IL‐2 felina parece ser uma opção de terapia segura. Embora a expressão de IL‐2 após a injeção do vetor e sua atividade biológica em equinos não tenham sido comprovadas neste estudo, o tratamento resultou em regressão e regressão parcial em 50% dos casos. Mais estudos são necessários para verificar esses achados e se estabelecer um protocolo de tratamento.